Protective efficacy of inactivated FHV-1 vaccine in cats following challenge with the Chinese field strains - Jiang, Yujie; Lai, Zhiying; Dai, Lingling; Deng, Yuan; Zhong, Lintao; Li, Shoujun; Lu, Gang (Frontiers in Veterinary Science, 2025)
Feline herpesvirus-1 (FHV-1) is a leading cause of feline viral rhinotracheitis (FVR), which mainly presents upper respiratory tract symptoms. Vaccination is the most effective strategy for controlling FHV-1. Prior to the initiation of this study, China does not have domestically produced commercially available FHV-1 vaccines using field strain as antigenic component and most corresponding imported vaccines contained feline viral rhinotracheitis, calicivirus, and panleukopenia (FVRCP) antigens. However, the protective efficacy of these vaccines against the prevalent FHV-1 strains in China remains unclear. In the present study, a total of 12 cats were randomly divided into 3 groups, which were vaccinated with FHV-1 field vaccine (Group 1 [an inactivated vaccine developed by ourselves using the Chinese field strain FHV-1 2020GD02]) and FVRCP vaccine (Group 2) and PBS (Group 3) as control, respectively. These animals received two vaccinations with a 21-day interval and were challenged with 2020GD02 at 21 days after the second vaccination. Clinical signs, serological responses, viral shedding, and histopathological changes were used to estimate protective efficacy of the two vaccines. Compared to Group 2, animals in Group 1 produced higher level FHV-1 antibody titers during immune processes. After challenge, Group 3 developed typical FVR. In contrast, animals in both Groups 1 and 2 showed significantly fewer clinical signs, viral shedding, and pathological changes, but could not provide complete protection. Our results provided a reference for further FHV-1 vaccines development in China.